Diuretics aggravate zinc deficiency in patients with liver cirrhosis by increasing zinc excretion in urine. Issue 4 (20th September 2012) - Chiba, Miho; Katayama, Kazuhiro; Takeda, Risato; Morita, Rie; Iwahashi, Kiyoshi; Onishi, Yoshiki; Kita, Hisaaki; Nishio, Akira; Kanno, Tomoyo; Saito, Tamiko; Maeda, Kosaku; Naito, Masafumi; et al.
<x xml:space="preserve">Abstract</x> Aim Liver cirrhosis is often accompanied by zinc deficiency. The exact mechanisms underlying zinc deficiency remain unclear. This study was undertaken to clarify the influence of diuretics on blood zinc levels and zinc excretion in urine in liver cirrhosis. Methods Seventy‐nine outpatients with liver cirrhosis were divided into four groups: (i) patients receiving no zinc preparations or diuretics (LC group); (ii) those receiving zinc preparations only (LCZ group); (iii) those receiving diuretics only (LCD group); and (iv) those receiving both zinc preparations and diuretics (LCDZ group). Among these groups, the effects of the administrated drugs on blood zinc levels and urinary zinc excretion were analyzed. Results Blood zinc levels were significantly lower in the LCD group (47.8 ± 10.5 μg/dL) than in the other groups (LC: 68.8 ± 17.1 μg/dL, P = 0.0056, post‐hoc test; LCZ: 78.4 ± 18.1, P < 0.0001; LCDZ: 70.3 ± 21.4, P = 0.0008). The creatinine‐adjusted urinary zinc excretion was significantly higher in the LCDZ group (548.1 ± 407.6 μg/mg creatinine) than in the other groups (LC, 58.5 ± 43.7; LCZ, 208.1 ± 227.8; LCD, 105.2 ± 154.4; each P < 0.0001). The fraction of urinary zinc excretion was also significantly higher in the LCDZ group (5.6 ± 2.9%) than in the other groups (LC, 0.6 ± 0.5; LCD, 1.7 ± 1.5; LCZ, 1.6 ± 1.2; each P < 0.0001). Conclusion In patients with liver cirrhosis, treatment with diuretics can increase zinc excretion by suppressing the reabsorption of zinc through renal tubules, which might lead to zinc deficiency.